Perancangan Dokumen Hazard Identification Risk Assessment and Risk Control (HIRARC) pada Proyek Otomasi Chiller Plant PT XYZ - Joshua Winata; Kriswanto Widiawan (Jurnal Titra, 2022)
PT XYZ is a company engaged in the service sector, namely the automation of the chiller plant system. There have been several work accidents at the PT XYZ project site. This final project was carried out using direct observation in the project field and interviews with field supervisors and employees. This final project aims to help companies to reduce the potential for work accidents that occur. From the result of the final project analysis, obtained 17 activites that are dangerous in the work process. Of the total 17 work accidents, severity is in the medium and high categories. 33 proposal for hazard risk control have been proposed, dominated by administrative control and PPE. Proposed control that has been given by the author and has been approved by the company. After the proposed control is given, the predicted severity of all 17 potential work accidents in the low category